2008
DOI: 10.1007/s10815-008-9278-2
|View full text |Cite
|
Sign up to set email alerts
|

Previous tubal ectopic pregnancy raises the incidence of repeated ectopic pregnancies in In Vitro fertilization-embryo transfer patients

Abstract: Purpose To investigate the incidence of Tubal Ectopic Pregnancies (TEP) in IVF-ET patients with respect to the status of the fallopian tubes after a previous TEP. Material and methods This retrospective study compares patients undergoing 481 IVF-ET cycles after conservatively or surgically treated TEP(s) with a Control Group (idiopathic or male factor for IVF-ET indication). Medical reports of surgery and/or hysterosalpingograms prior to the IVF cycles classified the status of the fallopian tubes. Results 12 T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 22 publications
2
29
3
Order By: Relevance
“…25 Similar to a previous report, 21 we saw a dose–response relationship between the risk of ectopic pregnancy and the number of embryos transferred during an ART cycle. Although earlier studies have not demonstrated this trend, 4,10,12,15 more recent investigations are consistent with our findings, 21,26 likely as a result of improvements in IVF techniques resulting in improved implantation potential, and increased odds of extrauterine implantation. Although the use of ultrasound guidance during embryo transfer procedures has increased since the late 1990s, a recent meta-analysis showed no improvement in ectopic pregnancy rates with its use.…”
Section: Discussionsupporting
confidence: 90%
“…25 Similar to a previous report, 21 we saw a dose–response relationship between the risk of ectopic pregnancy and the number of embryos transferred during an ART cycle. Although earlier studies have not demonstrated this trend, 4,10,12,15 more recent investigations are consistent with our findings, 21,26 likely as a result of improvements in IVF techniques resulting in improved implantation potential, and increased odds of extrauterine implantation. Although the use of ultrasound guidance during embryo transfer procedures has increased since the late 1990s, a recent meta-analysis showed no improvement in ectopic pregnancy rates with its use.…”
Section: Discussionsupporting
confidence: 90%
“…Prior treatment for EP, whether medical or surgical, may result in pathologic changes in tubal motility, ciliary function and uterine contractions [41]. (For fertility outcomes after prior EP, please see “Recurrence and future fertility”).…”
Section: Reviewmentioning
confidence: 99%
“…Weigert et al [16] investigated the influence of the condition of the fallopian tubes in women who experienced a tubal ectopic pregnancy in a previous pregnancy, on the incidence of a repeated tubal pregnancy in an IVF-ET cycle. Women with a prior tubal ectopic pregnancy significantly increased the risk per pregnancy for a further ectopic pregnancy even in IVF-ET (8.95 vs. 0.75%, P < 0.001), especially if they are smoking.…”
Section: Previous Ectopic Pregnancy Historymentioning
confidence: 99%